âBisnis Oriflame, Bisnis Konsultan Itu Sendiriâ: Budaya Organisasi Multilevel Marketing untuk Mewujudkan Mimpi - Kamawo, Deby Susan (ETNOSIA : Jurnal Etnografi Indonesia, 2016)
Multilevel marketing (MLM) is one of the marketing strategy which combines between distribution channel and direct selling to the consumers. One of the most popular MLM companies in Indonesia registered in the Indonesian Direct Sale Association (Assosiasi Penjualaan Langsung Indonesia, APLI) is PT. Orindo Alam Ayu, known as Oriflame, and is focused on beauty products. This article deals with Oriflameâs organisational culture by examining the organisational values and norms to achieve the companyâs vision and mission, and how the norms are practiced. The study indicates that in internalizing the values (togetherness, spirit, and passion) and norms of Oriflame (operational principles, conducting a four-in-one eventsâWelcome Party, Step-One, Step-Two and Meet-Up Team, and success plan through TRB), from which Oriflame consultants learn how âto achieve their dreamâ (mewujudkan mimpi). In such business, every consultant (upline as well as downline) is a working partner and they workin a complementary system, so that a consultantâs success is the success of others in the network. It is argued in this article that Oriflame is âan achievement dream businessâ that is developed on the basis of its values and norms. How much income and in what level of success plan are intended to achieve depend on the consultant itself because Oriflame business is âthe business of the consultant herself/himselfâ.